Metabonomics analysis of nonvolatile small molecules of beers during forced ageing. (6th March 2018) - Yao, Jiwei; Zong, Xuyan; Cui, Chun; Mu, Lixia; Zhao, Haifeng
Summary: Three kinds of beers with different degrees of ageing were used to examine their nonvolatile small molecules by a metabonomics approach based on ultra performance liquid chromatography coupled with quadrupole time‐of‐flight tandem mass spectrometry (UPLC‐Q‐ToF‐MS/MS). Results showed that a total of 2114 compounds were detected in forced‐aged beers with the positive mode of UPLC‐Q‐ToF‐MS/MS. There was a clear separation among three groups of beers with different degrees of ageing in principal component analysis (PCA) model. Sixteen potential metabolite markers related to beer oxidative stability were identified by orthogonal partial least‐squares discriminate analysis (OPLS‐DA). Results from the changes in the spectrum also indicated that some new compounds formed in beer during forced ageing. Thus, the proposed metabonomics approach is a powerful tool to give a fully understanding the ageing process of beer based on the identification of the markers related to oxidative stability. Abstract : Three kinds of beers with different degrees of ageing were used to examine their nonvolatile small molecules by a metabonomics approach based on ultra performance liquid chromatography coupled with quadrupole time‐of‐flight tandem mass spectrometry.